KAKUJOSHI NI DALAM KALIMAT BAHASA JEPANG - Ramdani, Suci; Nimashita, Hana; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research discussed about kakujoshi ni in Japanese sentences. The aim of this research is to know kakujoshi ni in Japanese language have an ability become proportion case marker and modal case marker according to Cook and Fillmore. The object of this research is Japanese sentence which have kakujoshi ni and verb. This research is a qualitative research which used descriptive method. As the result of this research, it is found that kakujoshi ni there are four of proportion case marker in Japanese language such as Agentive, Dative, Locative, Time and five of modal case marker in Japanese language such as Outer Benefactive, Outer Locative, Source of Modal case, Goal of Modal case, Time of Modal case, Result of Modal case. Beside that, this research find kakujoshi ni can be possible join to Active verb, Procces verb, and Stative verb.Key Word : Kakujoshi ni, Japanese Sentences